Gambaran Digital Skills Siswa SMK dalam Pembelajaran Berbasis Teknologi - Lammi, Muhammad Hidayat; Nooviar, Muh. Syilfa (Prodi Sistem Informasi UIN Alauddin, 2025)
– This study aims to describe the digital skills of vocational high school students in technology-based learning. The problem addressed is the limited ability of students to critically utilize digital technology, particularly in evaluating and verifying information sources. This study employs a qualitative descriptive method, with data collected through interviews and observations during the learning process. The collected data were analyzed descriptively to provide a comprehensive overview of students’ digital skills. The results show that most students demonstrate adequate skills in using digital technology and communication tools, including operating devices, accessing the internet, and utilizing learning platforms. However, their ability to critically evaluate information remains relatively low. Therefore, strengthening digital literacy, especially in critical thinking aspects, is necessary to ensure that students can effectively and responsibly use technology in learning activities.